METAFORA DALAM PUISI-PUISI GEORG TRAKL - VIRGIANA PUTRI MITANTI, MASHITA (UNIVERSITAS NEGERI SURABAYA, 2016)
Tags: poetry, metaphor, poetic means.                                                        One of the usage of literature is emotion, thought, and express feelings in the form of literary works, for example, Poem. To be able to express his emotion, thought and feelings, as the poet used special figurative language and choice of words as a means of his poetic imagination, for example, Metaphor. Metaphor is a means of poetic imagination or the rhetorical gesture, with the metaphor allows us to understand a thing or a process in terms of another thing or another operation. Georg Trakl is one the poet who often used metaphors in his poems. From those reason, the researcher studied the metaphor in the Trakl poems.                       Based on the explanation om  preface, the problems of this research are: 1). How is the metaphors that found in Georg Trakl poems ?, 2) How is the usage of poetic device in Georg Trakl poems to change conventional metaphor onto unconventional metaphor ?, and 3). To what terms do the metaphors in Trakl poems refer?. The purpose of this research are: 1). To describe the metaphorical domains that used Trakl in his poems, 2) To describe the poetic device that used in Trakl’s poems to change conventional metaphor unconventional metaphor, and 3). To find the metaphorical terms that imply Trakl in his poems.                       Kind of this research in this study is qualitative study. The primary data source used in this study are six choosen poems of Georg Trakl. The data are taken from metaphorical words, phrases, and sentences in Trakl poems.                       The results of this research show us that the dominant source domain of funds in Trakl poems are from (a) Plants; (b) light and darkness; (c) cooking and eating; (d) heat and coldness, then the dominant target domains are in terms of (a) life and death; (b) people; and (c) Religion. The poetic devicee that found in Georg Trakl’s poems are, are Extending, Elaborating, and Composing.